Compensation for Keeping Fossil Fuels in the Ground: Towards Equitable Restrictive Supply-Side Climate Policies - Schuch, Helena (Environmental ethics, 2025)
Restricting the supply of fossil fuels to mitigate climate change, instead of focusing on the demand only, is an idea that has recently gained traction in economics and policy research. This paper presents a moral argument for a specific supply restriction, namely a compensation mechanism to keep fossil fuels in the ground. By causing climate change, wealthier countries shrunk the extraction budget, such that poorer countries cannot extract their fossil fuels anymore without accelerating global warming. Therefore, countries with negligible historical responsibility for climate change, development needs, and no sufficient development alternatives are justified in demanding compensation if they forego extraction to mitigate climate change. Compensation could provide those countries with a way out of fossil fuel dependency. Translating this normative argument into a policy would require strong political will and carefully designed financing and transparency frameworks; however, there is precedent for such policies.